1980
DOI: 10.1159/000123109
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Rather Than Cyclic AMP as the Physiological Intracellular Regulator of Prolactin Release

Abstract: Studies on the mechanisms which govern the release of prolactin were undertaken using two in vitro techniques. A dispersed preparation of rat anterior pituitary cells was made by mechanical means in the presence of trypsin. These washed cells were drawn up into a small column together with a Bio-Gel matrix and perifused with Earle’s basic salt solution. The eluates containing prolactin were then collected at short intervals. Test substances were added to the perifusion medium and their effect on prolactin rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(50 citation statements)
references
References 25 publications
5
43
0
2
Order By: Relevance
“…Deuben (37,38), while our GRF extract demonstrated a dose-related increase in activity from 2 to 66 ng peptide/ml incubation medium, which suggests that it is active in the nanomolar range (Fig. 8) (39,40) (Fig. 8).…”
Section: Grf Activity In the Tumor Mediummentioning
confidence: 71%
“…Deuben (37,38), while our GRF extract demonstrated a dose-related increase in activity from 2 to 66 ng peptide/ml incubation medium, which suggests that it is active in the nanomolar range (Fig. 8) (39,40) (Fig. 8).…”
Section: Grf Activity In the Tumor Mediummentioning
confidence: 71%
“…THE ACTIONS of many peptide hormones are mediated by calcium [1][2][3][4][5][6][7][8] and the mechanism of action of GnRH on LH release also appears to involve calcium-dependent processes rather than cyclic nucleotides [9,10] . Recent studies have shown that the GnRH-induced response of cytosolic Ca2+ concentration ([Ca2+]i) is closely correlated with the secretory response [11] and that calcium influx through selective calcium channels is important in regulating the GnRH-induced…”
Section: Introductionmentioning
confidence: 99%
“…The action of TRH is mediated by calcium [14] and intracellular calcium-dependent processes play an important role in the mechanism of PRL release [15][16][17]. The TRH-stimulated increase in the cytosolic Ca2+ concentration ([Ca2+]i) is a major regulator of the secretory response [18].…”
Section: Introductionmentioning
confidence: 99%